Picnic of the boys of Wiltwyck School at Hyde Park with Eleanor Roosevelt. See also BG B25/419 - Norbin, Olga,
Picnic of the boys of Wiltwyck School at Hyde Park with Eleanor Roosevelt. See also BG B25/419.